Reimagined diabetic care approach: A qualitative study on the acceptability of mhealth interventions in a LMIC - Ola Sukkarieh; Leonard Egede; Mona Osman; Maya Bassil; Myrna A. A. Doumit (PLoS ONE, 2026)
Background Lebanon is a lower-middle income country in the MENA region that continues to be drained structurally by the socioeconomic upheaval. The estimated prevalence of T2DM in Lebanese adults is 9%. Despite the rapid growing use of mHealth and favorable health outcomes worldwide, the impact is understudied in Lebanon. Purpose Our study aimed to assess the acceptability of the use of mHealth intervention delivered via mobile phones that promotes diabetes self-management behaviors for Lebanese patients with T2DM. Design and Methods We used a descriptive qualitative approach for the study. Nine study participants were recruited based on purposeful and maximum variation sampling. Interviews were analyzed using the conventional content analysis. Results Analysis of the interviews revealed four major categories: (A) Transformative Approach to Care: Feeling Safe and Secure; (B) One Approach does not fit all; (C) Addressing psychological well-being; (D) Time and Economic gains. Conclusion This study provides compelling evidence that mHealth is highly acceptable among Lebanese adults with T2DM and offers significant potential to enhance diabetes care in LMICs. Participants embraced mHealth as a complementary tool that enhances communication, supports psychological well-being, and reduces financial barriers.